The Simonian bounded rationality hypothesis and the expectation formation mechanism - Kowalski, Tadeusz (Economics and Business Review, 2002)
In the 1980s and at beginning of the 1990s the debate on expectation formation mechanism was dominated by the rational expectation hypothesis. Later on, more interest was directed towards alternative approaches to expectations analysis, mainly based on the bounded rationality paradigm introduced earlier by Herbert A. Simon. The bounded rationality approach is used here to describe the way expectations might be formed by different agents. Furthermore, three main hypotheses, namely adaptive, rational and bounded ones are being compared and used to indicate why time lags in economic policy prevail and are variable. (original abstract)